The mystery of methylene blue and its role in managing post-cardiac surgery vasoplegic shock - Elbayomi, Mohamed; Dewald, Oliver; Pathare, Presheet; Kondruweit, Markus; Tandler, Rene; Weyand, Michael; Heim, Christian (Annals of Medicine, 2025)
Background: Vasoplegic syndrome is associated with high mortality. Methylene blue (MB) is a guanylate cyclase inhibitor that ameliorates this re-distributive type of shock. This study aims to investigate the outcome in patients who received MB early postoperatively. Methods: 2753 patients who underwent cardiac surgery utilizing cardiopulmonary bypass at our institution in a time interval of two years were identified. The incidence of vasoplegic syndrome was 7.2% (n = 200). Pharmacy records identified 84 patients (group 1, MB group) who received methylene blue and 116 patients (group 2, Control group) who didn’t receive the drug. This single-center retrospective cohort study’s primary outcome was in-hospital mortality. Secondary outcomes were postoperative hemodialysis, serum lactate levels at 24 h postoperatively, and intensive care unit stay length in days. Results: MB patients have a shorter ICU stay as compared to the control group (9 ± 8 days vs. 16 ± 6.9; p-value <.001). In the control group, postoperative hemodialysis was higher (20% in the MB group and 40% in the control group; p-value <.05). At 24 h post-op, the methylene blue group had reduced serum lactate levels (1.8 ± 1.2 vs. 4 ± 1.8 in the control group; p-value <.001). The methylene blue group had a decreased 24-hour norepinephrine dose (1.5 ± 1.2 vs. 2.8 ± 2 in the control group; p-value <.05). In-hospital mortality was not significantly different between the two groups (38% in the MB group vs. 43% in the control group). Conclusion: Early postoperative administration of methylene blue in patients with vasoplegic syndrome shortens intensive care unit stay and contributes to less end-organ damage.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Cardiopulmonary bypass; methylene blue; vasoplegic syndrome